2014
DOI: 10.1186/1756-0500-7-346
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impacted and transmigrated canine teeth in a Cypriote orthodontic population in the Northern Cyprus area

Abstract: BackgroundThe aim of this study was two-fold; (1) to evaluate the prevalence and patterns of impacted canines and transmigrated canine teeth, and (2) to evaluate the possible relationships between impacted teeth, malocclusions and systemic conditions in an orthodontic patient population.MethodsThe clinical records and panoramic radiographs of 453 patients [201 (44.3%) male and 252 (55.7%) female] referred to our outpatient clinic between January 2008 and January 2012 were retrospectively evaluated. The number,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
3
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 28 publications
2
25
3
7
Order By: Relevance
“…In a study by Sharma and Nagpal, 13 the incidence of TRC was found to be 0.66% in a sample of 3000 Indian subjects. In a study by Kamiloglu and Kelahmet, 14 in Cypriote population, a prevalence of 0.44% TRC was found. The frequency of transmigrated canines in the present study was found to be higher, i.e., 0.98%, which can be linked to the genetic, racial and ethnic differences.…”
Section: Discussionmentioning
confidence: 93%
“…In a study by Sharma and Nagpal, 13 the incidence of TRC was found to be 0.66% in a sample of 3000 Indian subjects. In a study by Kamiloglu and Kelahmet, 14 in Cypriote population, a prevalence of 0.44% TRC was found. The frequency of transmigrated canines in the present study was found to be higher, i.e., 0.98%, which can be linked to the genetic, racial and ethnic differences.…”
Section: Discussionmentioning
confidence: 93%
“…18 3500 ortodontik vakanın panoramik radyografi yardımıyla incelendiği çalışmalarında 16 (% 0.46) tanesinde mandibulada transmigrant kanine rastlandığını belirtmişlerdir. 18 Kamiloglu ve Kelahmet 5 Kıbrıs populasyonunda gömülü ve transmigre kanine ait yaptıkları araştırmada; 453 hastada 16 (% 3.53) gömülü kanin diş rapor etmiş, bunların da 2 (% 0.04) tanesinde sadece maksillada transmigre pozisyonda olduğunu bildirmişlerdir. 5 Çelebi ve ark.…”
Section: Discussionunclassified
“…18 Kamiloglu ve Kelahmet 5 Kıbrıs populasyonunda gömülü ve transmigre kanine ait yaptıkları araştırmada; 453 hastada 16 (% 3.53) gömülü kanin diş rapor etmiş, bunların da 2 (% 0.04) tanesinde sadece maksillada transmigre pozisyonda olduğunu bildirmişlerdir. 5 Çelebi ve ark. 19 dental anomalileri değerlendirdikleri çalışmalarında gömülü kanin dişleri içerisindeki transmigrasyon oranı % 27,7 olarak belirlenmiştir.…”
Section: Discussionunclassified
“…In a study conducted by Kamiloglu et al 28 , prevalence of mandibular transmigration was found 0.44%. Shah et al 6 scanned 7886 patients and found the transmigration rates as 0.1% for mandibular canines.…”
Section: Discussionmentioning
confidence: 99%
“…These are observation, surgical extraction, transplantation, bringing to the original position of the unerupted canine by surgical and orthodontic treatment 18,27,28,30 .…”
Section: Discussionmentioning
confidence: 99%